The Relationship between Insect Resistance and Tree Age of Transgenic Triploid Populus tomentosa Plants - Ren, Yachao; Zhang, Jun; Wang, Guiying; Liu, Xiaojie; Li, Li; Wang, Jinmao; Yang, Minsheng (Frontiers in Plant Science, 2018)
To explore the stability of insect resistance during the development of transgenic insect-resistant trees, this study investigated how insect resistance changes as transgenic trees age. We selected 19 transgenic insect-resistant triploid Populus tomentosa lines as plant material. The presence of exogenous genes and Cry1Ac protein expression were verified using polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) analyses. The toxicity for Clostera anachoreta and Lymantria dispar was evaluated by feeding fresh leaves to first instar larvae after the trees were planted in the field for two years and after the sixth year. Results of PCR showed that the exogenous genes had a long-term presence in the poplar genome. ELISA analyses showed significant differences existed on the six-year-old transgenic lines. The insect-feeding experiment demonstrated significant differences in the mortality rates of C. anachoreta and L. dispar among different transgenic lines. The average corrected mortality rates of C. anachoreta and L. dispar ranged from 5.6 to 98.7% and 35.4 to 97.2% respectively. The larval mortality rates differed significantly between the lines at different ages. Up to 52.6% of one-year-old transgenic lines and 42.1% of two-year-old transgenic lines caused C. anachoreta larval mortality rates to exceed 80%, whereas only 26.3% of the six-year-old transgenic lines. The mortality rates of L. dispar exhibited the same trend: 89.5% of one-year-old transgenic lines and 84.2% of two-year-old transgenic lines caused L. dispar larval mortality rates to exceed 80%; this number decreased to 63.2% for the six-year-old plants. The proportion of six-year-old trees with over 80% larval mortality rates was clearly lower than that of the younger trees. The death distribution of C. anachoreta in different developmental stages also showed the larvae that fed on the leaves of one-year-old trees were killed mostly during L1 and L2 stages, whereas the proportion of larvae that died in L3 and L4 stages was significantly increased when fed on leaves of six-year-old trees. Results of correlation analysis showed there was a significant correlation between the larvae mortality rates of trees at different ages, as well as between Cry1Ac protein contents and larvae mortality rates of six-year-old trees.